1992
DOI: 10.1084/jem.176.5.1355
|View full text |Cite
|
Sign up to set email alerts
|

Oral tolerance to myelin basic protein and natural recovery from experimental autoimmune encephalomyelitis are associated with downregulation of inflammatory cytokines and differential upregulation of transforming growth factor beta, interleukin 4, and prostaglandin E expression in the brain.

Abstract: SummaryExperimental autoimmune encephalomyelitis (EAE) in the Lewis rat is a self-limited inflammatory process localized to the central nervous system that is induced by the injection of myelin basic protein (MBP) in adjuvant . Oral administration of MBP suppresses EAE, and this suppression is mediated by CD8+ T cells that adoptively transfer protection and suppress both in vitro and in vivo by the release of transforming growth factor (TGF) (3 after antigen-specific triggering. Furthermore, oral tolerance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
319
1
4

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 664 publications
(335 citation statements)
references
References 49 publications
11
319
1
4
Order By: Relevance
“…In conclusion, our findings are in agreement with other studies, where TGF-b has been found to mediate the active suppression responsible for oral tolerance [15][16][17][18]. However, this is the first time TGF-b production has been demonstrated in situ, in response to parenteral challenge with a previously orally given heterologous antigen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In conclusion, our findings are in agreement with other studies, where TGF-b has been found to mediate the active suppression responsible for oral tolerance [15][16][17][18]. However, this is the first time TGF-b production has been demonstrated in situ, in response to parenteral challenge with a previously orally given heterologous antigen.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies suggest that TGF-b may be the key cytokine that mediates active suppression [7,16,17], but to our knowledge it has only once been shown that TGF-b is being produced in vivo in nontransgenic animals-in response to an orally given autologous antigen in the rat experimental autoimmune encephalitis model [18]. Therefore, we decided to investigate the presence of TGF-b in situ in our system, where we have observed a suppressed inflammatory response of the draining lymph node, due to the presence of a heterologous antigen to which the animal previously had been orally tolerized.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,[30][31][32][68][69][70][71][72] The current study demonstrates, for the first time, the appearance of 'natural' antiself antibodies to a key pro-inflammatory cytokine, TNF-␣, during the development of a T cell-mediated autoimmune disease of the CNS. These antibodies developed in rats immunized with p68-86/CFA and not with the CFA alone (Figure 3), even though both groups exhibited an extensive local inflammatory process at the site of CFA immunization.…”
Section: Figure 6 Tnf-␣-specific Antibodies Produced By Dna Vaccinatimentioning
confidence: 66%
“…This type of control has been termed peripheral tolerance. T cell anergy, 69 active suppression, 31,[68][69][70] T cell deletion 93,94 and generation of anti-idiotypic immunity 95 have been described as key mechanisms that contribute to the maintenance of peripheral tolerance. The current study suggests, for the first time, that self-specific T and B cells, capable of mounting self-specific immunity against pro-inflammatory mediators, escape central tolerance to provide the immune system with a powerful tool with which it keeps its dangerous anti-self activity under control and thus maintains tolerance to self in the periphery.…”
Section: Figure 6 Tnf-␣-specific Antibodies Produced By Dna Vaccinatimentioning
confidence: 99%
“…[8][9][10] This may represent restoration of a more balanced immune response to auto-antigen stimulation and result in disease amelioration. Although alteration of effector function of a differentiated CD4 + T cell appears to be unlikely, 11,12 it appears to be possible to modulate the effector function and differentiation of undifferentiated Th0 T cells and CD4 + T cells that are not completely differentiated.…”
Section: Introductionmentioning
confidence: 99%